2020
DOI: 10.3897/folmed.62.e47932
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Immune Response Against Helicobacter pylori in Infused BALB/c Mice by pcDNA3.1(+)-ureA 

Abstract: Background: The purpose of the present study was to produce a pcDNA3.1(+)-ureA recombinant vector and evaluate the capacity of this vector to stimulate the immune response against H. pylori infection in infused BALB/c mice.    Materials and methods: The pcDNA3.1(+)-ureA construct was prepared and transformed into E. coli, successfully. The animals we used in the study were allotted into three groups for infusion of 1) recombinant plasmid, 2) pcDNA3.1(+)-ureA + nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Moreover, H. pylori CagA reduces the secretion of IL-12p40, and increases the expression of IL-10, which shows pro- and anti-inflammatory effects, promoted by this oncoprotein [ 37 ]. In mice that were treated with the recombinant proteins rUreB, rCagA, or pcDNA3.1(+)-ureA plasmid from H. pylori , it was found that these molecules increase the secretion of IFN-γ, IL-17A, and TGF-β1 with a concomitant IL-4 diminished production and that CD4+ T-cells preferentially differentiated into Th1 and Th17 lymphocyte subpopulations; these events are characteristic of gastric inflammation [ 38 , 39 , 40 ]. In patients with non-ulcer dyspepsia, gastritis or peptic ulcers that were infected by H. pylori , a high secretion of IL-17, IFN-γ, IL-23, IL-6, IL-10, TNF-α, IL-21, IL-8, and IL-37 was reported [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, H. pylori CagA reduces the secretion of IL-12p40, and increases the expression of IL-10, which shows pro- and anti-inflammatory effects, promoted by this oncoprotein [ 37 ]. In mice that were treated with the recombinant proteins rUreB, rCagA, or pcDNA3.1(+)-ureA plasmid from H. pylori , it was found that these molecules increase the secretion of IFN-γ, IL-17A, and TGF-β1 with a concomitant IL-4 diminished production and that CD4+ T-cells preferentially differentiated into Th1 and Th17 lymphocyte subpopulations; these events are characteristic of gastric inflammation [ 38 , 39 , 40 ]. In patients with non-ulcer dyspepsia, gastritis or peptic ulcers that were infected by H. pylori , a high secretion of IL-17, IFN-γ, IL-23, IL-6, IL-10, TNF-α, IL-21, IL-8, and IL-37 was reported [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“… 34 Most studies have used urease as a candidate antigen, such as Nasr-Esfahani et al, who showed that injecting the recombinant plasmid pcDNA3.1 (+)- ureA into mice can stimulate an immunoresponse in an animal model infected with H. pylori . 35 Intranasal immunization with recombinant UreB vaccine with plant polysaccharides as adjuvants protected mice from H. pylori infection, which may be related to increased gastrointestinal specific SIgA and Th1/Th17 CD4 + T-cell response. 36 Most of the vaccines that have entered the clinical research stage contain urease antigen.…”
Section: Antigensmentioning
confidence: 99%